Patent foramen ovale (PFO) and migraine: role of platelet Tissue Factor expression and oxidative stress. The LEARNER study. (3rd October 2022) - Camera, M; Brambilla, M; Canzano, P; Becchetti, A; Conti, M; Teruzzi, G; Porro, B; Muratori, E; Tedesco, C; Montorsi, P; Bartorelli, A; Tremoli, E; et al.
Abstract: Background: Migraine is a chronic neurovascular disorder with a multifactorial aetiology. A strong relationship links migraine with aura (MHA) and patent foramen ovale (PFO), with migraine regression after PFO closure. Increased platelet aggregation and oxidative stress were documented in migraineurs. Current guidelines suggest the use of aspirin or P2Y12-antagonists. To date, however, no clear mechanisms connecting MHA to PFO has been demonstrated. Purpose: To perform a comprehensive analysis of platelet activation, inflammation and oxidative stress status in 78 aspirin-treated MHA-patients before (T0) and 6-months after (T1) PFO closure (LEARNER Study-NCT03521193-clinicaltrials.gov). Primary endpoint was migraine regression rate in relation to these parameters. Methods: P-selectinpos-, activated-glycoproteinIIbIIIa (aGPIIbIIIa)pos-, Tissue Factor (TF)pos-, reactive oxygen species (ROS)pos-platelets, platelet-leukocyte aggregates (PLA) and microvesicles (MVs) were evaluated by flow cytometry; thrombin generation (TG) by Calibrated Automated Thrombogram (CAT) assay; oxidative stress status by mass spectrometry. Twelve aspirin-treated-healthy subjects (HS) were enrolled for comparison. To test the effect of PFO patients' plasma on platelet activation, blood from HS was plasma-depleted and replaced with a pool of plasma from PFO patients. Results: Migraine resolution occurred in 69.7%, significant reduction in 27%, while no effect was observed in 2 patients (3.2%). Only ROSpos-platelets, and TFpos-platelets and -MVs were significantly higher at T0, sustaining a TG capacity that was associated with an altered blood GSSG/GSH (Oxidized/Reduced Glutathione) ratio. This phenotype reverted to HS levels at T1 (Fig. 1). MHA-PFO plasma, added to HS blood, mirrored the in vivo platelet activation and N-acetylcysteine blunted it. In vitro GSSG treatment of HS platelets reproduced the in vivo condition. Aspirin had little effect on the platelet prothrombotic phenotype which was effectively inhibited by a P2Y12-antagonist (Fig.2). Conclusions: MHA-PFO patients show a platelet-associated prothrombotic phenotype, characterized by a marked thrombin generation capacity sustained by an elevated number of platelets and MVs expressing a functionally active Tissue Factor and sustained by altered oxidative stress status. This phenotype, not fully controlled by aspirin but by P2Y12-antagonism, reverted after PFO closure together with a complete migraine remission. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Italian Ministry of Health